Research and development on Japanese Antarctic Research Expedition uniform - Tsukie Izuhara; Masaru Ayukawa (National Institute of Polar Research, 2008)
The design of wear for Japanese Antarctic Research Expedition (JARE) members was investigated. Wear must be loose-fitting because JARE members perform may kinds of operations. Heat must be able to escape easily. Considering that measures to deal with sweat and frost are necessary, synthetic fibers such as polyester and nylon wear used and treated to increase breathablity, water resistance, resistance to static electricity, and thermal insulation. We produced wear appropriate for JARE members including researchers and research support staff, who need clothing that is both highly functional and in a style appropriate for intellectual pursuits.